UTILIZATION OF DEBT COLLECTOR SERVICES IN DEBT SECURED WITH FIDUSIA IN PANDEMIC PERIOD AFTER THE VERDICT OF THE CONSTITUTIONAL COURT NO. 18/PUU-XVII/2019 - Fani Martiawan Kumara Putra (Perspektif, 2020)
Fiduciary guarantee institutions are guarantee institutions that are in great demand in Indonesia, in fact it is very possible that Fiduciary is currently the most widely used guarantee institution besides three other security institutions in Indonesia, namely Gadai, Hipotek and Hak Tanggungan. Determination when the default debtor, has its own rules, can not be interpreted arbitrarily, then in a pandemic like this, determining the default debtor certainly also needs to consider the economic conditions of many parties that decline, then it means, whether the use of debt collectors is still a matter that is worthy of attention to these two aspects. This is a normative legal research. The result of this research is that the Constitutional Court’s ruling drew many interpretations, one form of which was that the Fiduciary guarantee was no longer familiar with parate executies, and sales were underhanded, but had to go through the court. Even though the decree also emphasized default. This decision must be interpreted in full, not only related not to execute it, but also to understand about the default. Thus, will be clear what the purpose of the ruling of the constitutional court. This will also be useful for law enforcement on the civil debt relationship during this pandemic. Leasing as an institution that provides credit to the public, still requires classification rules for customers who can apply for credit. So that cases of customers who are negligent in debt payments and have problems with debt collectors do not occur.